Mopomulo dan Semarak Kebersamaan: Akselerasi Potensi SDM Desa Leyao Melalui Program KKS-T IAIN Sultan Amai Gorontalo - aprianda masilu; Yayang Tia Nadila Sulaiman; Yuwin Rustam Saleh; Muflihah Nurkamiden; Adinda Nawai; Alda Fadhila; Nuraisah; Defrin Mane; Muh. Ansar Antukai (Madani: Jurnal Pengabdian Ilmiah, 2026)
Leyao Village faces complex challenges, including limited digital infrastructure, high school dropout rates, and ecological threats due to industrial activities. This study aims to describe the implementation of the 2026 IAIN Sultan Amai Gorontalo Thematic Social Work Lecture (KKS-T) program in accelerating Human Resource (HR) potential and social strengthening in Leyao Village. Using a qualitative method with a field research approach, data were collected through participatory observation and documentation during the service period. The results show that the KKS-T program successfully integrated four main aspects: (1) Ecological aspects through the “Mopomulo” (planting) movement as a response to flood threats; (2) Educational as pects through seminars on preventing sexual harassment and bullying; (3) Religious and administrative aspects through "Religious Classes" and village boundary arrangements; and (4) Social aspects through "Semarak Kebersamaan" activities. The synergy between students, village governm ent, and the Youth Organization (Karang Taruna) proved effective in increasing public critical awareness and strengthening social capital. In conclusion, egalitarian collaboration between academics and local elements is key to triggering a shift in community mindset toward a more independent, religious, and ecologically resilient village.